2008
DOI: 10.2478/s11687-008-0008-1
|View full text |Cite
|
Sign up to set email alerts
|

Helminth parasites of the pupfish Cyprinodon meeki (Pisces: Cyprinodontiformes), an endemic freshwater fish from North-Central Mexico

Abstract: A total of 21 pupfish Cyprindon meeki was collected from the spring Abraham González, Durango, Mexico. Seven helminth taxa were recovered: Salsuginus angularis, Posthodiplostomum minimum, Clinostomum complanatum, Bothriocephalus acheilognathi, Cyclustera cf. ralli, Atactorhynchus duranguensis and Spiroxys sp. Among them, B. acheilognathi and A. duranguensis were the most frequent and abundant species. The remaining species were rare and found at low mean abundance. The observed species richness, individual par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…The infracommunities studied herein were generally species-poor (on average, only 1-2 species of helminth per fish) and were dominated by the monogenean Urocleidoides vaginoclaustrum. This is consistent with infracommunities reported for other freshwater fishes in México (Martínez-Aquino et al, 2004Martínez-Aquino and Aguilar-Aguilar, 2008). Kennedy (1989) suggested that infracommunities with low rates of colonization, low numbers of species and of individuals, and with low or no presence of interspecific interactions is a general pattern in freshwater fishes.…”
Section: Discussionsupporting
confidence: 89%
“…The infracommunities studied herein were generally species-poor (on average, only 1-2 species of helminth per fish) and were dominated by the monogenean Urocleidoides vaginoclaustrum. This is consistent with infracommunities reported for other freshwater fishes in México (Martínez-Aquino et al, 2004Martínez-Aquino and Aguilar-Aguilar, 2008). Kennedy (1989) suggested that infracommunities with low rates of colonization, low numbers of species and of individuals, and with low or no presence of interspecific interactions is a general pattern in freshwater fishes.…”
Section: Discussionsupporting
confidence: 89%
“…Parasite communities of both species of cyprinids are depauperate and are dominated by one helminth species; this, and the fact that a low species richness values at both, the component community and infracommunity levels, were detected, is consistent with the parasite community structure in a diverse array of freshwater fishes inhabiting in epicontinental waters in central and northern Mexico, corresponding with the Nearctic region (Peresbarbosa- Rojas et al, 1994;Espinosa-Huerta et al, 1996;Rojas et al, 1997; Pérez-Ponce de León et al, 2000;Martínez-Aquino et al, 2004, 2007Martínez-Aquino & Aguilar-Aguilar, 2008;Romero-Tejeda et al, 2008). Helminth parasite communities in the 2 cyprinids we studied herein also show a numerical dominance by a single or a few helminth species.…”
Section: Helminth Communitiessupporting
confidence: 63%
“…Nearly all Cyprinodon have a diet composed mainly of algae and detritus. We verified this with an exhaustive literature search of all studies with dietary data or observations of Cyprinodon (e.g., Cox 1972; Davis 1981; Naiman 1975; Naiman 1979; Minckley and Minckley 1986; Martinez‐Aquino and Aguilar‐Aguilar 2008; Stoike and Pister 2010; Carson 2009) as well as information from FishTraits (Frimpong and Angermeier 2009; Miller et al 2005).…”
Section: Methodsmentioning
confidence: 94%